Pengaruh Self-Directed Learning terhadap Cognitive Presence Mahasiswa Unisba dalam pembelajaran E-learning - Rifa Auliarahmi; Susandari (Bandung Conference Series: Psychology Science, 2022)
Abstract. In online learning such as E-Learning, students must be able to learn independently. Therefore, it is necessary to have individual characteristics that are able to bring up independent learning in online learning. These characteristics can be referred to as Self-Directed Learning. The purpose of this study is to find out how much influence Self-Directed Learning has on the Cognitive Presence of Unisba students in E-learning learning. The method used is the causality method using a quantitative approach. The research sample consisted of 377 students who were determined using Cluster Random Sampling taken from 7 Faculties in the Social Sciences Study Program. The measuring instrument used to measure Self-Directed Learning in students is using the Self-Directed Learning Aptitude Scale from Abd-El-Fattah (2010) and to measure Cognitive Presence the researcher uses the Community Of Inquiry measuring instrument from Shea & Bidjerano (2010). The results show that 65.5% of students have high self-directed learning. The Cognitive Presence phase with the highest score was Exploration (84.35%) and the lowest score phase was Triggering Event (47.75%). Data analysis used a simple linear regression test technique. The results of the study stated a significance value of 0.00 <0.05 which indicates a significant influence of Self-Directed Learning on Cognitive Presence in Unisba students. The results of data analysis show that the Self-Directed Learning variable contributes to the Cognitive Presence variable by 28.3%. Abstrak. Pada pembelajaran online seperti E-Learning, siswa harus mampu belajar mandiri. Maka dari itu diperlukan karakteristik individu yang mampu memunculkan kemandirian belajar dalam belajar online. Karakteristik tersebut bisa disebut sebagai Self-Directed Learning. Tujuan penelitian ini yaitu untuk mengetahui seberapa besar pengaruh Self-Directed Learning terhadap Cognitive Presence mahasiswa Unisba dalam pembelajaran E-learning. Metode yang digunakan yakni metode kausalitas dengan menggunakan pendekatan kuantitaif. Sampel penelitian terdiri dari 377 mahasiswa yang ditetapkan menggunakan Cluster Random Sampling yang diambil dari 7 Fakultas dalam Program Studi Ilmu Sosial. Alat ukur yang digunakan untuk mengukur Self-Directed Learning pada mahasiswa yaitu menggunakan Self-Directed Learning Aptitude Scale dari Abd-El-Fattah (2010) dan untuk mengukur Cognitive Presence peneliti menggunakan alat ukur Community Of Inquiry dari Shea & Bidjerano (2010). Hasil menunjukan bahwa 65,5% mahasiswa memiliki Self-Directed Learning yang tinggi. Fase Cognitive Presence dengan skor tertinggi yaitu Exploration (84,35%) dan fase skor terendah yaitu Triggering Event (47,75%). Analisis data menggunakan teknik uji regresi linier sederhana. Hasil penelitian menyatakan nilai signifikansi sebesar 0,00 < 0,05 yang menunjukan adanya pengaruh yang signifikan dari Self-Directed Learning terhadap Cognitive Presence pada mahasiswa Unisba. Hasil analisis data menunjukkan bahwa variabel Self-Directed Learing berkontribusi terhadap variabel Cognitive Presence sebesar 28.3%.